Canonical analysis of neuroendocrine-metabolic and neuroendocrine-immune relationships at female rats - Mel’nyk, Oksana; Zukow, Walery; Hrytsak, Myroslava; Popovych, Dariya; Zavidnyuk, Yuriy; Bilas, Volodymyra; Popovych, Igor (Journal of Education, Health and Sport, 2021)
Background. It has been shown before that drinking mineral waters of different composition has a significant effect on the neuroendocrine, metabolic and immune parameters of healthy rats. We analyzed the canonical correlations between neuroendocrine parameters, on the one hand, and metabolic and immune parameters, on the other hand. Materials and Methods. Experiment was performed on 58 healthy female Wistar rats 240-290 g. HRV parameters, major adaptation hormones, metabolism and immunity parameters were recorded. Results. The method of canonical correlation analysis revealed causal relationships between neuroendocrine and metabolic and neuroendocrine and immune parameters of the organism. The degree of neuroendocrine determination of individual sets of metabolic parameters ranges from 60% to 92%, and immune status from 87% to 96,5%. Conclusion. Effects of mineral waters on metabolism and immunity are realized through nervous and hormonal mechanisms.